Collaborative Practice between Doctors and Nurses in Patients Management: Attitude of Teamwork - Wiwik Kusumawati; Romdzati Romdzati (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background:  Interprofessional collaboration is essential in providing higher-quality health services and ensuring patient safety.Objective: This study aims to assess the attitude of cooperation between doctors and nurses as first line health workers in an academic health facility and explore their perspectives on the collaboration attitude between doctors and nurses.Methods: This study used a mixed-method design. The quantitative sample was chosen randomly but with total sampling for the primary clinic. Data on the attitude of cooperation between doctors and nurses from the questionnaire results were analyzed descriptively. The sample for the qualitative study was selected purposively, each health service consisted of 1 doctor and one nurse, so the number of informants was six. The qualitative data were transcribed verbatim and analyzed qualitatively using the constant comparative method.Results: The results showed that of 84 respondents, 54 doctors, and 30 nurses, 95% showed a good teamwork attitude. Some respondents (5%) showed a bad attitude, especially on three items, namely item no 4 (doctors do not have the right to change the treatment plan that has been made), 13 (doctors do not have to be the final determinant) and 18 (possibility of other professions to become leaders). The results of the qualitative analysis show that there are five final themes, namely: 1. teamwork is good; 2. the role of the profession; 3. the importance of interprofessional communication; 4. openness to receive feedback; 5—patient safety and PCC.Conclusion: Both professions have distinct but equal and complementary roles in patient management, each with their own advantages or capabilities. Open communication, which includes getting criticism, can help overcome a poor cooperative attitude.